2018
DOI: 10.1016/j.vaccine.2017.12.079
|View full text |Cite
|
Sign up to set email alerts
|

Explanations for the high potency of HPV prophylactic vaccines

Abstract: HPV L1 virus-like particle (VLP) vaccines administered in a prime/boost series of three injections over six months have demonstrated remarkable prophylactic efficacy in clinical trials and effectiveness in national immunization programs with high rates of coverage. There is mounting evidence that the vaccines have similar efficacy and effectiveness even when administered in a single dose. The unexpected potency of one dose of these VLP vaccines may largely be attributed to structural features of the particles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
150
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 65 publications
1
150
0
5
Order By: Relevance
“…The vaccine achieves strong herd protection even at relatively low coverage, and the benefits of vaccination were substantially augmented in Australia by the large scale catch‐up program . If a single dose of HPV vaccine proves adequate for protection (as some observational data suggest), effective vaccine coverage is already high (greater than 85% for Indigenous girls and 80% for Indigenous boys in all four jurisdictions). Modelling indicates that sustained coverage exceeding 80% in both sexes will eventually achieve local elimination of vaccine‐targeted HPV types …”
Section: Discussionmentioning
confidence: 99%
“…The vaccine achieves strong herd protection even at relatively low coverage, and the benefits of vaccination were substantially augmented in Australia by the large scale catch‐up program . If a single dose of HPV vaccine proves adequate for protection (as some observational data suggest), effective vaccine coverage is already high (greater than 85% for Indigenous girls and 80% for Indigenous boys in all four jurisdictions). Modelling indicates that sustained coverage exceeding 80% in both sexes will eventually achieve local elimination of vaccine‐targeted HPV types …”
Section: Discussionmentioning
confidence: 99%
“…The idea that HPV vaccines could possibly be effective with only 1 dose, unlike traditional subunit protein vaccines, originally arose from post hoc analyses of the bivalent HPV vaccine trial, which showed equal efficacy against infection among women who did not complete the course . The strong immunogenicity of the vaccines may be underpinned by the antigen display provided by the virus‐like particles, which provide spacing of the antigen to the immune system that is equivalent to antigen presentation by the actual virus . Initial observational data from vaccination programs did not support equivalent 1‐dose protection against genital warts or cervical disease, but such data may have been confounded by potentially higher risk characteristics of women who only ever received 1 or 2 doses of an intended 3‐dose course (ie, women noncompliant with the vaccine program [amplified by the monitoring of outcomes among the initial catch‐up populations of already infected women]) and by the inherent bias that prevalent infection/disease is more likely to become apparent coincidently with the earlier doses in a vaccine course .…”
mentioning
confidence: 99%
“…11,12 The strong immunogenicity of the vaccines may be underpinned by the antigen display provided by the virus-like particles, which provide spacing of the antigen to the immune system that is equivalent to antigen presentation by the actual virus. 13 Initial observational data from vaccination programs did not support equivalent 1-dose protection against genital warts or cervical disease, but such data may have been confounded by potentially higher risk characteristics of women who only ever received 1 or 2 doses of an intended 3-dose course (ie, women noncompliant with the vaccine program [amplified by the monitoring of outcomes among the initial catch-up populations of already infected women]) and by the inherent bias that prevalent infection/disease is more likely to become apparent coincidently with the earlier doses in a vaccine course. 14 More recently, an interrupted randomized controlled trial in India, which has become a de facto observational cohort because some girls received only 1 of 2 or 3 planned doses, has suggested equivalent 1-dose quadrivalent vaccine effectiveness against infection.…”
mentioning
confidence: 99%
“…While the reduced dose number could facilitate course completion, Brotherton and her colleagues note that the wider spacing of doses (6–12 months) than in the 3‐dose schedule (6 months) could affect coverage, particularly among Indigenous adolescents, for whom school absenteeism rates are high. We therefore need to understand and reduce any barriers to course completion, although recent evidence suggests that HPV vaccines may be adequately effective when administered as a single dose …”
mentioning
confidence: 99%
“…We therefore need to understand and reduce any barriers to course completion, 3 although recent evidence suggests that HPV vaccines may be adequately effective when administered as a single dose. 4 Early successes of the HPV vaccination program have already been documented, including large falls in the prevalence of HPV and genital warts among both Indigenous and non Indigenous Australians. 3 Sustaining the current high rates of initiation and increasing course completion by Indigenous adolescents should lead to substantial falls in cervical cancer incidence and mortality over the next two decades.…”
mentioning
confidence: 99%